Pitfalls and perils for smaller portfolios: an analysis of the financial behaviour of retail investors - Somer, Jonathan de (2021)
Pitfalls and perils for smaller portfolios: An analysis of the financial behaviour of retail investors analyses the main biases that retail investors are affected by and how it influences their actions on the financial market. It does so by comparing data on trends with the stocks both in retail investor portfolios and price of cryptocurrencies.